Transferência intergovernamental do cota-parte do icms aos municípios do estado do paraná: análise dos critérios de produção agropecuária e fator ambiental - Ferreira , Rafael Maximiano (2018)
The present study aimed to understand the process of composition of the indices of Agricultural Production and Environmental Factor that constitute the criteria for distribution of the resources of the share of ICMS (Brazilian state Tax on Circulation of Goods and Transportation and Communication Services) of the state of Paraná. For that, the theoretical foundation addresses the theme of fiscal federalism, which is about state’s organization; intergovernmental transfers and their motivations. In addition, we discuss the structure of the participation rate of municipalities in ICMS (share of ICMS), presenting the criteria used to make this intergovernmental transfer. The present study was developed according to the qualitative and quantitative approaches. Descriptive analysis of the data was used, together with the exploratory analysis of the data, through the analysis of main components. The period analyzed is the composition of the participation index of the municipalities in ICMS for the tax year of 2018. The population studied is composed of all 399 municipalities of the state of Paraná. The results showed that the mesoregions West, Central North and Southwest, as the main agricultural producers of Paraná, are also the largest beneficiaries of the resources of the share, transferred by the criterion of Farming and Cattle Raising. The Farming and Cattle Raising matrix for 2016, which is the basis for the distribution of the resources of the share of ICMS in tax year of 2018, was composed of 347 products, which belong to three major segments: Agriculture, Cattle raising and Forestry. It was verified the concentration of Farming and Cattle Raising production in 20 products, which are responsible for 81.09% of Paraná's production in this segment. The analysis of main components highlighted the importance of cereals and soybean in Agricultural activity. In Cattle raising activity, the components that have the greatest explanatory power are pig farming and milk production. The exploitation of yerba mate (Ilex paraguariensis), laminated wood and pine nuts (Araucaria angustifolia) were the most relevant for the Forestry activity. Regarding the Environmental Factor, the analysis occurred in an isolated manner for each of the variables that integrate this criterion. The Conservation Units totaled 1,766,718 ha (4365655,25335 acres), and are distributed in 19 management categories, which have levels of private, municipal, state or federal management. The difference in area extension of the Iguaçu National Park is evident, and the fact that 195 municipalities do not have Conservation Units registered with the Environment Institute of Paraná (IAP), what makes it impossible to transfer resources by this criterion to the municipalities. The Drinking Water Source Protection Fund is the most dissimilar difference, since 315 municipalities are not benefited by this compensatory policy. It was observed a high concentration of transfers of these resources to the metropolitan mesoregion of Curitiba, especially to the municipality of Piraquara. It is worth noting the opportunities for the municipalities to manage the criteria for allocating resources from the share of ICMS, through alignment between public policies and the engagement of rural producers, especially in the areas of legal reserve (RL) and areas of permanent protection (APP) that can be converted into private reserves of the natural heritage (RPPN), thus contributing to the evolution in the amounts passed through the criterion of Environmental Factor.